THE SECOND LANGUAGE INFLUENCE ON FOREIGN LANGUAGE LEARNERS’ ERRORS: THE CASE OF THE FRENCH LANGUAGE FOR ALGERIAN STUDENTS LEARNING ENGLISH AS A FOREIGN LANGUAGE - Hanafi, Aissa (European Scientific Journal, ESJ, 2014)
Various researchers have concentrated on those errors which demonstrate the influence of one’s native language to second language acquisition. Some would consider them as inhibitory while others pointed out that they are facilitative. The present study shed light on another sphere of interference errors that occur in tri-lingual societies. The scope of the study was narrowed to focus on the role performed by the French language in the frequency of errors made by the Algerian students in their English as Foreign Language (EFL) learning. The study adopted a contrastive approach to discover whether this role is inhibitory or facilitative. The plain task was to give students a text to translate from French to English( version A) .The students were then asked to translate the same text from Arabic to English(version B).A chart was designed to compare the frequency , the type and the degree of severity of errors in both versions of translation. The analysis of the results in the chart showed that the students made less number of errors in the version (A) translation compared with version (B).Hence, the role of the French language in The EFL learning for Algerian students seems rather facilitative.